Associations between trauma and substance use among healthcare workers and public safety personnel during the SARS-CoV-2 (COVID-19) pandemic: the mediating roles of dissociation and emotion dysregulation - Patel, Herry; Easterbrook, Bethany; D'Alessandro-Lowe, Andrea M.; Andrews, Krysta; Ritchie, Kimberly; Hosseiny, Fardous; Rodrigues, Sara; Malain, Ann; O'Connor, Charlene; Schielke, Hugo; McCabe, Randi E.; Nicholson, Andrew A.; et al. (European journal of psychotraumatology, 2023)
Background: Given the highly stressful environment surrounding the SARS-CoV-2 pandemic, healthcare workers (HCW) and public safety personnel (PSP) are at an elevated risk for adverse psychological outcomes, including posttraumatic stress disorder (PTSD) and alcohol/substance use problems. As such, the study aimed to identify associations between PTSD severity, related dissociation and emotion dysregulation symptoms, and alcohol/substance use problems among HCWs and PSP. Methods: A subset of data (N = 498 ; HCWs = 299 ; PSP = 199 ) was extracted from a larger study examining psychological variables among Canadian HCWs and PSP during the pandemic. Structural equation modelling assessed associations between PTSD symptoms and alcohol/substance use-related problems with dissociation and emotion dysregulation as mediators. Results: Among HCWs, dissociation fully mediated the relation between PTSD and alcohol-related problems (indirect effect β = .133, p = .03) and emotion dysregulation partially mediated the relation between PTSD and substance-related problems (indirect effect β = .151, p = .046). In PSP, emotion dysregulation fully mediated the relation between PTSD and alcohol-related problems (indirect effects β = .184, p = .005). For substance-related problems among PSP, neither emotion dysregulation nor dissociation (ps >.05) had any effects. Conclusion: To our knowledge, this is the first study examining associations between PTSD severity and alcohol/substance use-related problems via mediating impacts of emotion dysregulation and dissociation among HCWs and PSP during the SARS-CoV-2 pandemic. These findings highlight dissociation and emotion dysregulation as important therapeutic targets for structured interventions aimed at reducing the burden of PTSD and/or SUD among Canadian HCWs or PSP suffering from the adverse mental health impacts of the SARS-CoV-2 pandemic. Among healthcare workers, dissociation mediated relation between posttraumatic stress disorder (PTSD) severity and alcohol-related problems and emotion dysregulation mediated relation between PTSD severity and substance-related problems. Among public safety personnel, emotion dysregulation mediated relation between PTSD severity and alcohol-related problems. Neither dissociation nor emotion dysregulation mediated relation between PTSD severity and substance-related problems. Results underscore dissociation and emotion dysregulation as potential key therapeutic targets for intervention for healthcare workers and public safety personnel struggling with PTSD and comorbid alcohol/substance use-related problems.